국내 오픈뱅킹 품질요소가 사용자 이용의도에 미치는 영향분석 - 정보천; Bo-chun Jung; 홍석기; Suk-ki Hong (Inteonet jeongbo hakoe nonmunji = Journal of Korean Society for Internet Information, 2021)
금융업의 주요 채널이 모바일로 빠르게 변화하는 추세이다. 이러한 환경에서 은행들은 자사의 경쟁력 확보를 위해 정보통신기술을 이용하는 방안에 대해 많은 관심을 기울이며 특히 지급결제 분야에서 빠른 혁신이 추진되고 있다. 국내도 금융결제망의 개방형 전환, 간편 결제의 이용한도 확대 등 금융혁신을 가속화하기 위해 2019년 10월 오픈뱅킹서비스를 실시하였다. 본 논문은 국내 오픈뱅킹서비스의 품질요소가 이용의도에 미치는 영향에 관해 실증연구를 진행하였다. 오픈뱅킹을 구성하는 서비스 품질요소를 인터페이스 디자인, 혁신성, 보안성, 데이터 공유성으로 분류하고 기술수용모형(TAM)을 활용하여 인지된 편의성과 유용성, 이용의도에 유의미한 영향을 미치는지 검증하였다. 검증결과 혁신성과 보안성은 편의성과 유용성에 유의미한 영향을 미치지 못하였으나 인터페이스 디자인과 데이터 공유성은 인지된 편의성에 영향을 미치는 것으로 파악되었다. 연구결과는 학계와 더불어 오픈뱅킹서비스를 도입하려는 기업들에게 이용자의 서비스 이용품질에 관한 시사점을 제공한다. The main channels of the financial industry are rapidly changing to mobile. In this environment, banks are focusing on information and communication technology to secure their competitiveness, and rapid innovation is being pursued especially in the payment settlement sector. In October 2019, Korea also introduced open banking services to accelerate the financial innovation, such as the open conversion of financial settlement networks and the expansion of the use of simple payments. In this paper, an empirical study was conducted on the effect of domestic open banking quality factors on usage intention. The service quality factors for open banking were classified into interface design, innovation, security, and data sharing, and the technology acceptance model (TAM) was used to verify whether it has a significant effect on perceived convenience, usefulness and intention to use. According to the analysis results, while innovation and security did not have a significant effect on convenience and usefulness, interface design and data sharing were found to have an effect on perceived convenience. The results would provide implications for some quality issues for companies seeking to introduce open banking services as well as for the related academic arena.